Diagnostic Study of the Formation of the Aesthetic Development of Primary Education Students in the Process of Teaching the Russian Language - Sobirjanovna, Dustova Dildora; Fayzullayevich, Abdullaev Sayfulla (European Journal of Life Safety and Stability (2660-9630), 2021)
This article reveals some aspects of the formation of the aesthetic culture of students in the process of teaching the Russian language. A diagnostic study of the formation of the aesthetic development of primary education students in the process of teaching the Russian language was carried out.